Factors affecting Y Generation buying life Takaful Insurance / Siti Noratikah Abdullah - Abdullah, Siti Noratikah (2015)
Takaful is defined as an Islamic insurance which is a concept whereby a group of participants a mutually agree to donate each other (tabarru') if one of them are having a loss or damage. Takaful operator will distribute funds to participants in the event of loss or damage if it is happen. This research is about the factors affecting Y generation buying life takaful insurance. The dependent variable is buying behaviour of Y generation, while the independent variable is knowledge, awareness, promotion and income level. The objective of the study are to identify the major factor affecting Y generation buying life takaful insurance, secondly are to determine the significant relationship between Y generations with life takaful insurance. Last but not least, to provide some recommendations and suggestion to improve factors affecting Y generation buying life takaful insurance. The data was set in this research are collected from Y generation which is student UiTM KBM and people surrounding in area Bandaraya Melaka through questionnaires. 70 people were selected from that area as a respondent. At the end of this research, the researcher provides some suggestion that in the future researchers can use as an example the study.